Susceptibility of Apis mellifera (Hymenoptera: Apidae) to pellitorine, an amide isolated from Piper tuberculatum (Piperaceae) - Miranda, José Ednilson; Navickiene, Hosana Maria Debonsi [UNESP]; Nogueira-Couto, Regina Helena [UNESP]; De Bortoli, Sérgio Antônio [UNESP]; Kato, Massuo Jorge; Bolzani, Vanderlan da Silva [UNESP]; Furlan, Maysa [UNESP] (Springer Nature, 2003)
The acute toxicity of pellitorine, an amide isolated from Piper tuberculatum (Piperaceae) which is studied as a biopesticide in European corner borer, was evaluated on larvae and newly emerged adults of honeybee Apis mellifera by means of contact and ingestion bioassays. Workers in the larval and adult phase were separated in groups, which received pellitorine in different concentrations. The larvae were maintained in their own original cells, receiving feeding and normal care from the nurses. The adults were confined in wooden cages with screens, receiving artificial diet made up of sugar and water (1:1). The concentrations of 40, 200, 1 000, 5 000 and 25 000 ng a.i./individual were obtained diluting pellitorine in 98% ethanol. LD10 values of 39.14, 36.16 and 13.79 ng a.i./insect were determined for larvae, for adults by ingestion and adults by contact, respectively. The honeybee larvae were shown to be highly susceptible to the amide pellitorine.
Keywords: Apis mellifera; Biopesticide; Contact; Ingestion; Pellitorine; Toxicity; biopesticide; honeybee; nontarget organism; toxicity; Apidae; Hymenoptera; Insecta; Piper swartzianum; Piperaceae